Simple Matrix encryption scheme with variable ciphertext length - Zhong WANG; Yiliang HAN (网络与信息安全学报)
Multivariable public key cryptography is one of the reliable candidates for anti-quantum cryptography.The Simple Matrix scheme is constructed using the operations between three matrices.An improved version of the Simple Matrix scheme was proposed.It is constructed by using two flat matrices with random quadratic polynomials,so that the rank attacks is infeasible for the new scheme,and the algebraic attacks breaks the system is at least as hard as solving a set of random quadratic equations.The new scheme will improve the proportion of ciphertext and plaintext to 2 times or more,break the fixed proportion of ciphertext and plaintext,so that it has a flexible proportion to adapt to different needs.